Path Analysis on the Biopsychosocial Determinants of Type 2 Diabetes Mellitus and Depression at Dr. Moewardi Hospital, Surakarta - Esty Budiarti; Didik Gunawan Tamtomo; Rita Benya Adriani (Masters Program in Public Health, 2018)
Background: Diabetes Mellitus (DM) is a a major disease that is threatening global population health. This disease ranks third by global public health priority. The incidence of type 2 DM in 2014 was 442 million patients worldwide. Indonesia is one of 10 countries with high DM incidence. The incidence of type 2 DM in Indonesia in 2014 was 10 million patients. This study aimed to examine the biopsychosocial determinants of type 2 Diabetes Melitus and depression at Dr. Moewardi Hospital, Surakarta, using path analysis.Subjects and Method: This was an analytic and observational study with case control design. The study was conducted at Dr. Moewardi Hospital, Surakarta, from August to October, 2017. Sample consisting of 100 patients type 2 DM and 100 non DM patients were selected for this study by fixed disease sampling. The dependent variable was type 2 DM. The independent variables were body age, mass index, education level, occupation, stres, family income, comorbidity, activity, and family history of type 2 DM. The data were collected using medical record and questionnaire. The data were analyzed by path analysis.Results: The risk of type 2 DM increased with higher body mass index (b= 2.66; 95% CI= 1.41 to 3.91; p<0.001), higher income (b=-0.93; 95% CI= -1.90 to 0.045; p=0.062), older age (b= 2.88; 95% CI= 0.62 to 5.15; p= 0.013), presence of DM family history (b= 2.56; 95% CI= 1.45 to 3.68; p <0.001), and comorbidity (b= 3.25; 95% CI= 2.07 to 4.43; p<0.001). The risk of depression increased by type 2 DM (b= 1.032; 95% CI= 0.42 to 1.63; p= 0.001). Body mass index increased with higher physical activity (b= -1.41; 95% CI= -2.03 to -0.79; p<0.001). Income increased with high education level (b= 2.58; 95% CI= 1.83 to 3.33; p<0.001). High physical activity increased with occupation (b=0.96; 95% CI= 0.38 to 1.53;p= 0.001).Conclusion: The risk of type 2 DM increased with higher body mass index, higher income, older age, presence of DM family history, and comorbidity.Keyword: biopsychosocial determinants, type 2 DM, depressionCorrespondence: Esty Budiarti. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email:estybudiarti21@gmail.com.Journal of Epidemiology and Public Health (2018), 3(1): 1-14https://doi.org/10.26911/jepublichealth.2018.03.01.01